Needs-adapted Data Presentation in e-Information Tools - Henning Bergenholtz (Woordeboek van die Afrikaanse Taal-WAT, 2012)
In the current debate about the status of lexicography there are at least three quite different opinions: (i) Lexicography does not have or need any kind of own theory but can use all relevant linguistic theories. (ii) Lexicography needs a special theory for the lexicographical praxis, but this discipline is still a part of linguistics. (iii) Lexicography is a genuine part of information science and can use theories and learn from practice in the information society, but it also needs special theories for lexicography. It is the third opinion we will maintain in this paper by discussing the information needs in the information society and partly using the function theory of lexicography.